An academic writing model: Lessons learned from experienced writers - Fahrus Zaman Fadhly; Muziatun Muziatun; Nanan Abdul Manan; Arrofa Acesta; Dadang Solihat (Indonesian Journal of Applied Linguistics, 2023)
Academic writing seems daunting for novice writers. Unveiling cognitive processes of experienced writers in academic writing can presumably aid novice writers, primarily writing for publication. The purpose of this research is to explore the cognitive processes of experienced writers who have published articles in reputable journals in writing scientific articles. Three experienced writers participated in the study: one from the social science and two from the STEM fields. Thematic analysis following the six phases of Braun and Clark (2006) was conducted to analyze the interview data from three experienced writers. The findings from the interview generated five themes: search, topic, research, writing, and publication. These emerging themes have similarities with the previous academic writing models but expand some actions toward the publication process. The themes reflected the steps taken by the experienced writers who participated in the study in producing their published articles. Thus, these steps can be used as one of the models to guide novice writers intending to publish their work in academic journals.Academic writing seems daunting for novice writers., and Uunveilingthe cognitive processes of experienced writers in academic writing can presumably aid novice writers, primarily writing for publication. The purpose of this research is to explore the cognitive processes of experienced writers who have published articles in reputable journals in writing scientific articles. Three experienced writers participated in the study: one from the social science and two from the STEM fields. Thematic analysis following the six phases of Braun and Clark (2006) was conducted to analyze the interview data from three experienced writers. The findings from the interview generated five themes: search, topic, research, writing, and publication. These emerging themes have similarities with the previous academic writing models but expand some actions toward the publication process. The themes reflected the steps taken by the experienced writers who participated in the study seem to employ the steps reflected in the themes in producing their published articles. Thus, these steps this model can be used as one of the models to guideguidelines for novice writers intending to publish their work in academic journals.